The Effect of Supply Chain Management on Operational Performance of Furniture Industry in Jombang Regency - Via Kusuma Wardani; Fien Zulkarijah; Aniek Rumijati (Universitas Muhammadiyah Malang, 2021)
This study aimed to determine the effect of supply chain management (supplier partnership, information sharing, customer relationship) on the operational performance of the furniture industry in Jombang Regency, and to find out the dominant variables that influenced the operational performance. The population and sample in this study were all furniture business owners in Mojowarno Sub-District, Jombang Regency. The total population was 163 and the total sample was 62 respondents. The data collection was conducted by distributing questionnaires to furniture business owners. In this study, the analytical tools used were scale range, multiple linear regression analysis, and a dominance test that showed that supply chain management with supplier partnership, information sharing, and customer relationship variables significantly influenced the operational performance. The dominant variable influencing operational performance was the customer relationship.